A systems biology approach to investigate control targets of intracellular calcium transients induced by Clostridium perfringens Phospholipase C - Brenes Guillén, Laura Natalia (2018)
Clostridium perfringens phospholipase C (CpPLC) plays a key role in the pathogenesis of gas gangrene, an acute and life-threatening infection in humans. CpPLC leads to the unregulated production of second messengers, such as calcium, and activates important signaling pathways like PKC, MEK, and NFkB, inducing ROS production, that leads towards cellular damage. We propose a systems biology approach to identify potential microRNAs which could be used as tools to explore the role of calcium channels in the mechanism of action of CpPLC, and eventually as therapeutic agents that render cells less sensitive to this toxin. Results show that miR19B1 and miR449B are interesting candidate targets which perturbations may affect the expression of genes involved in calcium transport. This approach may be useful to elucidate calcium molecular interactions involved in the CpPLC mechanism of action.